Entrepreneurial Motivations and Capabilities of Migrant Entrepreneurs in Australia. (11th April 2018) - Rametse, Nthati; Moremong‐Nganunu, Topoyame; Ding, Ming Juan; Arenius, Pia
Abstract: This article presents findings on immigrant entrepreneurship in Australia. The relationship between the entrepreneurial start‐up motivation, co‐ethnic preferences and entrepreneurial capabilities of established immigrant businesses are explored. We analyse data collected with a self‐administered survey questionnaire from 157 immigrant entrepreneurs in Melbourne's suburbs. Our findings show that immigrant entrepreneurs who report a high level of individual achievement as their start‐up motivation also report high levels of entrepreneurial capabilities in terms of opportunity recognition, managerial innovativeness and proactiveness . Immigrant entrepreneurs who are highly influenced by co‐ethnic preferences on staff employment and customer targeting report higher opportunity recognition than those who have a co‐ethnic preference on suppliers . We provide important insights and explanations for these findings and their implications for Australian immigrant entrepreneurs and policymakers.